A Case of Chronic Periaortitis with Retroperitoneal Fibrosis - Park, Sun Hee (The Korean Society of Cardiology, 2012)
A 73-year-old man with a history of hypertension and ascending aortic dissection was hospitalized for aggravated abdominal pain and general ache for 3 months. Follow-up CT showed aggravated abdominal aortic hematoma with aneurysm, atherosclerotic periaortitis and bilateral hydronephrosis. An initial laboratory finding showed elevated levels of inflammatory markers and renal dysfunction. Positron emission tomography-CT showed an increased standardized uptake values level in the aortic arch, descending thoracic aorta, major branch, abdominal aorta, and common iliac artery. For bilateral hydronephrosis, a double J catheter insertion was performed. Tissue specimens obtained from previous surgery on the aorta indicated the infiltration of lympho-plasma cells without granuloma formation in the aortic wall. After a combined therapy of high dose steroid therapy with azathioprine, the patient's initial complaints of abdominal pain, weakness and azotemia improved. This case was diagnosed as chronic periaortitis based on aortic inflammation at biopsy, which was complicated with retroperitoneal fibrosis and ureteric obstruction.